2016
DOI: 10.1292/jvms.15-0544
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of preventive effect of sildenafil and therapeutic effect of sildenafil treatment in rats with monocrotaline-induced pulmonary arterial hypertension

Abstract: This study aimed to investigate the potential effects of sildenafil on pulmonary hypertension (PH) in the monocrotaline (MCT)-induced PH rat. Twenty-four, 12-week-old, male Sprague-Dawley rats were injected with MCT or saline solution. After injection of MCT, rats received oral sildenafil immediately (early-phase treatment group: E group), 4 weeks after injection (late-phase treatment group: L group) or no treatment (MCT group) until 6 weeks after injection. Serial echocardiography and right ventricular systol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that MCT injection in rats resulted in enhanced RVSR, mPAP, RVH, increased pulmonary vessel wall thickness and PAH. These changes mainly lead to the development of PAH ( Yoshiyuki et al, 2016 ; Karpuz et al, 2017 ). In this study, we used MCT-induced PAH rat model to evaluate the effect of maprotiline.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that MCT injection in rats resulted in enhanced RVSR, mPAP, RVH, increased pulmonary vessel wall thickness and PAH. These changes mainly lead to the development of PAH ( Yoshiyuki et al, 2016 ; Karpuz et al, 2017 ). In this study, we used MCT-induced PAH rat model to evaluate the effect of maprotiline.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that these models produce distinct RV responses in terms of adaptive RV hypertrophy in the PAB model, in contrast to the maladaptive failure in the SuHx and MCT models ( 28 , 149 ). Several characteristics of maladaptive RV remodeling in the PAH model have been proposed, including RV dilation, reduced function, fibrosis, and capillary rarefication ( 29 , 150 ). However, as of the confounding effects of potentially altered pulmonary vascular resistance, hypoxia, molecular modulation (e.g., VEGF inhibition), or toxins on RV function, the MCT and SuHx models cannot be used to investigate isolated RV effects of potential therapies, and the PAB model is relevant in this regard ( 29 , 151 , 152 ).…”
Section: Surgical Modelsmentioning
confidence: 99%